KEBERHASILAN USAHA TANI KOPI TEPAL MELALUI MANAJERIAL PETANI - Fitriyani, Ika; Rahayu, Sri; Sudiyarti, Nining (Wakil Rektor 3, Direktorat Pengabdian kepada Masyarakat dan Publikasi, Universitas Teknologi Sumbawa, 2021)
The problem faced by Tepal coffee farmers is the limited/lack of facilities and infrastructureproduction infrastructure (processing and packaging machines), lack of resource allocationwhich is not in accordance with the profits achieved, the capital is smallcompared with vegetable, rice and corn farming. This study aims toknowing the success of Tepal coffee farming through farmer management. This researchusing quantitative methods with qualitative and quantitative data types. AmountThe respondents of this research are 82 farmers who grow coffee in 2020. As forThe main variables in this study are farmer management and farming successTepal Coffee. The analysis technique uses descriptive. The results of this study showthat the success of the Tepal coffee farmers' business through farmer management is to provideunderstanding of their business opportunities, leveraging the experience of coffee farmersTepal and flexible farming management facilities, providing counselingand training to obtain information, using local materials asmeans of production, has a favorable production cost and combinesinternal strength to improve product sales and marketing. Governmentregions through the related technical services are expected to pay more attention to coffee farmers andprovide good service through the provision of training and technical counselingregularly/periodically to improve coffee farming and provide adequate capitaladequate.